Transformation as relational mobilisation: The networked geography of Addis Ababa's sustainable transport interventions. (April 2021) - Grandin, Jakob; Haarstad, Håvard
Literatures on sustainability transition and transformation increasingly emphasise the role of spatiality and local agency. This paper argues that relational thinking has much more to offer this debate than presently acknowledged, particularly in revealing the geographical interconnections between dispersed nodes of action and innovation. We use relationality to show the interconnections at work in exchanging and negotiating sustainability interventions between cities and across scales. Using the mass transit planning process in Addis Ababa as a point of entry, we trace how the city's transformation is negotiated at the intersection of local agency, the Ethiopian national political setting and international networks. A host of actors from different scales come together as transformation is assembled by aligning extensive local experience with elements mobilised from elsewhere. This relational mobilisation perspective arguably infuses hope into the debate, because it opens new ways of identifying seemingly insignificant actions and actors elsewhere and recognising them as potential drivers of change.